Mathematical model of the problem of network planning of industrial tasks at an enterprise - D. A. Pavlov; I. M. Yakhontova (Новые технологии)
A mathematical model of the problem of network distribution of production problems at an enterprise has been studied. A specific class of scale-invariant graphs, called pre-fractal graphs is used as a model of an hierarchical structure of an organization divisions. As a result, the task of distributing production problems is reduced to the problem of covering a prefractal graph with simple non-intersecting chains in a multi-criteria formulation.